2022
DOI: 10.3389/fimmu.2022.918223
|View full text |Cite
|
Sign up to set email alerts
|

Fibroblasts: Immunomodulatory factors in refractory diabetic wound healing

Abstract: Diabetes is a systemic disease in which patients with diabetes may develop peripheral neuropathy of the lower extremities and peripheral vascular disease due to long-term continuous exposure to high glucose. Delayed wound healing in diabetes is one of the major complications of diabetes. Slow wound healing in diabetic patients is associated with high glucose toxicity. When the condition deteriorates, the patient needs to be amputated, which seriously affects the quality of life and even endangers the life of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(45 citation statements)
references
References 126 publications
(42 reference statements)
0
30
0
Order By: Relevance
“…Under the diabetic condition, the inflammation period is prolonged and sustained, delaying wound healing [ 23 ]. Compared with inflammation, fibrosis and neoangiogenesis occur at a relatively later stage [ 25 , 26 ], and are inhibited upon DM [ 26 ]. In the present study, DM was found to induce a prominent inflammatory state in D7 and to inhibit fibrosis and neoangiogenesis in D16 ( Figure 3 , Figure 5 , and Figure 7 ), confirming the temporal specificity of different pathophysiological processes in diabetic wound healing.…”
Section: Discussionmentioning
confidence: 99%
“…Under the diabetic condition, the inflammation period is prolonged and sustained, delaying wound healing [ 23 ]. Compared with inflammation, fibrosis and neoangiogenesis occur at a relatively later stage [ 25 , 26 ], and are inhibited upon DM [ 26 ]. In the present study, DM was found to induce a prominent inflammatory state in D7 and to inhibit fibrosis and neoangiogenesis in D16 ( Figure 3 , Figure 5 , and Figure 7 ), confirming the temporal specificity of different pathophysiological processes in diabetic wound healing.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, hyperglycemia inhibits cell migration and proliferation, resulting in vascular damage, hypoxia, abnormal accumulation of extracellular matrix (ECM), delayed re-epithelialization, and excessive scar formation (Figure 2). [3,26,27]…”
Section: Diabetic Chronic Wound (Dcw) Microenvironmentmentioning
confidence: 99%
“…These ulcers not only cause significant physical and psychological pain to patients but also impose a DOI: 10.1002/adfm.202308387 substantial burden on the economy and society as a whole. [1][2][3] Under typical conditions, the process of wound closure is an intricate and meticulously orchestrated physiological phenomenon comprising four interrelated and sequential stages: hemostasis, inflammation, proliferation (re-epithelialization), and remodeling (scar maturation). These stages overlap and work in harmony to ensure proper healing of the wound.…”
Section: Introductionmentioning
confidence: 99%
“…Perpetuated inflammatory states induced by increased mast cell degranulation[ 33 ], excessive extracellular traps produced by neutrophils[ 34 ], dysregulated and persistent M1 (pro-inflammatory) macrophage polarization[ 35 ], pro-inflammatory factors (IL-1ÎČ, TNF-α, and IL-6) overexpression, and anti-inflammatory factors (IL-10 and TGF-ÎČ) deficiency finally hinder wound healing[ 7 ]. The proliferative phase of diabetic wound healing is characterized by disturbed physiological functions of keratinocytes[ 36 ], fibroblasts[ 37 ], and endothelial cells[ 38 ], then the impaired re-epithelialization, granulation tissue formation, matrix deposition, and angiogenesis affect wound healing. Various factors also affect the function and activity of these cells during this phase, including decreased chemokines with pro-angiogenesis produced by macrophages, hemoglobin glycation, vascular stenosis, increased oxygen consumption affecting oxygen-dependent cellular behaviors, and impaired nerve fiber regeneration[ 7 , 31 , 39 , 40 ].…”
Section: Dcws: Healing Disorders Caused By Various Mechanismsmentioning
confidence: 99%